O atendimento ao cidadão e o portal da Câmara dos Deputados [manuscrito] - Nakamura, Paula Mari Mikai (2013)
The research was conducted, in general, to reach an analysis of the conditions of the intermediation between the Chamber of Deputies and society through the use of the web portal